Strategies for Developing Social Science Education Curricula Within the Modern Digital Era - Ari Hidayat; Nurul Zaman (Journal of Smart Pedagogy and Education, 2025)
This research examines strategies for developing social science curricula in the digital age, focusing on Indonesia’s Kurikulum Merdeka. Utilizing a qualitative review of Scopus-indexed literature (2020–2025), the study addresses the shift from rote content mastery toward critical digital literacy. Key theoretical frameworks, including Connectivism and the Digital Pedagogy for Sustainable Educational Transformation (DP4SET) model, are analyzed to inform curriculum redesign. The findings highlight significant systemic challenges, particularly the digital divide in frontier (3T) regions and the need for updated teacher competencies like AI-TPACK. Subject-specific strategies, such as Geographic Information Systems (GIS) and digital archives, are identified as vital for fostering higher-order thinking. The report concludes that a sustainable curriculum must balance technological integration with humanistic values, recommending a hybrid approach that explicitly teaches digital skills while embedding them across disciplines. Ultimately, the goal is cultivating digital wisdom to prepare students for a complex, post-truth global society through robust, transformative education.